A Study of suicidal ideation in different subgroups within a sexual minority by assessing variables that may reflect subjective experience of distress among minorities - Parihar, Akash; Kumar, Nitin; Sharma, Sandeep; Raj, Lakhan (International Journal of Psychosocial Rehabilitation, 2020)
INTRODUCTION: A discord between natal role and gender identity, poor self and societal acceptance of one’s sexual orientation/gender identity, physical, verbal and sexual abuse and discrimination, from family, friends, and peers during and after coming out, fear of law-enforcement, loneliness, and lack of coping mechanisms and healthy role models can lead to poor physical and mental health outcomes among the LGBTQ youth in India. For sexual minority people, sexual orientation-related discrimination and prejudice might be associated with feelings of thwarted belongingness. Given that perceived burdensomeness, thwarted belongingness and Psych-ache. have been associated with SI in other populations, included sexual minority.Methodology: - Advertisement in form of Flash banners will be generated on websites, forums and social media related to sexual minority. Within the advertisement, volunteers who were at least 18 years of age (no other inclusion criteria) were invited to complete a survey that took approximately 20 min to finish. The Flash Banner containing the performa for Thwarted belongingness and perceived burdensomeness, Suicidal ideation, The Psych-ache Scale.Result & Conclusion: Interpersonal construct perceived burdensomeness, which accounts for some increased prevalence of suicidal ideation for adult gay men, lesbian women, and bisexual men and women. Clinicians can utilize this information by using cognitive and behavioural interventions to decrease perceived burdensomeness and, thus, decrease suicide risk for sexual minority adult clients